Collectively Exhaustive Hybrid Triboelectric Nanogenerator Based on Flow‐Induced Impacting‐Sliding Cylinder for Ocean Energy Harvesting. Issue 3 (4th December 2021) - Kim, Ji‐Seok; Kim, Junyoung; Kim, Jong‐Nam; Ahn, Junseong; Jeong, Jun‐Ho; Park, Inkyu; Kim, Daegyoum; Oh, Il‐Kwon
Abstract: For the sustainable application of remote sensing and monitoring in the ocean environment, energy harvesting technology based on flow‐induced vibration is in the spotlight. Herein, based on the flow‐induced self‐excitation of an impacting‐sliding cylinder, a collectively exhaustive hybrid triboelectric nanogenerator (TENG) is reported, that utilizes both freestanding‐sliding (FS) and contact‐separation (CS) modes. Most importantly, the flow‐induced impacting cylinder (FIC) between two side walls is newly implemented to resolve the critical problem of the lock‐in phenomena occurring in conventional vortex‐induced vibration systems of circular cylinders. Owing to the presence of two side walls, the FIC based TENG (FIC‐TENG) shows a stable electrical power generation in a wide range of flow velocity (0.05–1.02 m s −1 ) without lock‐in phenomena. In addition, the collectively exhaustive FIC‐TENG can be used to continuously produce electric power utilizing both FS and CS hybrid modes. The energy harvesting performance is greatly enhanced by adopting nanopatterns on triboelectric surfaces in the CS mode TENG and a frequency upconversion effect of interdigitated electrodes in the FS mode TENG, resulting in proper remote operation of a wireless fidelity thermometer. Abstract : A flow‐induced impacting cylinder‐based hybrid mode triboelectric nanogenerator (FIC‐TENG) has great potential to effectively convert hydrokinetic energy in a wide range of flow velocity into electricity to address the lock‐in limitation. The energy harvesting performance of the FIC‐TENG improves due to line nanopatterns and interdigitated electrodes for large effective contact area and frequency upconversion, respectively.